Modified fiber-fly ash-based geopolymer cementing material and preparation method thereof

Through the use of modified fiber-fly ash polymer cementitious materials, the high energy consumption and carbon emission problems of cement-based cementitious materials when strengthening weak soil layers are solved, and the preparation of high-performance cementitious materials is realized, with significant environmental protection and mechanical advantages.

CN119707370APending Publication Date: 2025-03-28DONGHUA UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411899210.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When using cement-based cementitious materials to reinforce weak soil layers, the prior art has problems of high energy consumption and high carbon emissions, which have multiple negative impacts on the ecological environment.

Method used

Modified fiber-fly ash base polymer gelling material is used to form a gelling material with high performance by mixing the modified fibers with fly ash, steel slag, and slag, and slag.

Benefits of technology

This material can effectively reduce carbon emissions and energy consumption, has satisfactory mechanical properties, is suitable for soft soil reinforcement, and after using modified fibers, the material's crack resistance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707370A_ABST
    Figure CN119707370A_ABST
Patent Text Reader

Abstract

The invention discloses a modified fiber-fly ash-based geopolymer cementing material and a preparation method thereof. The modified fiber-fly ash-based geopolymer cementing material comprises 40-60 parts of fly ash, 15-35 parts of slag, 10-30 parts of steel slag, an exciting agent accounting for 4-20 parts of the mass of the cementing material, 30-38 parts of water accounting for the mass of the cementing material and 0-2 parts of agent modified fiber accounting for the mass of the cementing material. The modified fiber-fly ash-based geopolymer cementing material prepared by the method is a low-carbon material, the solid waste resource fly ash can be effectively utilized, meanwhile, the risk of solid waste stockpiling and discharging is reduced, and the modified fiber-fly ash-based geopolymer cementing material can be used for manufacturing various green building material products. The economical problems of solid waste resource storage and resource application can be effectively solved; part of cement is replaced to solidify soft soil; a high-performance material with condensation flow characteristics and mechanical strength characteristics is simple and economical in material taking, rapid and convenient to construct and reliable and stable in curing effect; the modified fiber is introduced, so that the mechanical property is better improved, and the curing effect is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource recycling and green low-carbon cementitious materials, and in particular to a modified fiber-fly ash-based polymer cementitious material and a preparation method thereof. Background Art

[0002] Fly ash is an important solid waste emitted after coal-fired power generation is burned in the boiler. With the development of the national power industry and the increase in electricity consumption, the emission of fly ash in the flue gas of thermal power plants has also continued to rise, so it is particularly important to strengthen the utilization of fly ash. Fly ash is often grayish white, powdery particles. The main component of fly ash is Al2O3 hydration to form silicon (aluminum) oxygen tetrahedrons and steel slag hydration to release a large amount of Ca 2+ Ions combine to form cementitious substances. Steel slag and fly ash have a synergistic effect and are often widely used in concrete mineral admixtures and cement active mixed materials. The excellent properties of fly ash make it have a wide range of application value. Especially in the field of construction, fly ash and its waste slag have a synergistic effect to form geopolymer cementitious substances that have a gelling and filling effect on engineering materials, etc., and have broad application prospects.

[0003] Steel slag is a by-product derived from the process of smelting pig iron. It is gray-black in color with steel slag powder. Its raw material particle size is uneven and its surface is relatively rough. With the continuous growth of demand for industrial steel, the scale of steel production in my country has expanded rapidly. As a by-product of the steelmaking process, the emission of steel slag has also increased sharply. The remaining steel slag is piled up in large quantities, occupying land area and causing pollution to water resources, atmospheric environment and soil. However, steel slag can be used as a potential choice for high-quality aggregates due to its wear resistance, anti-skid and high alkalinity. It is also a hydraulic admixture that can form a gel material through an alkaline activator to play a mosaic and filling role in the gaps between soil particles. Therefore, steel slag can be used as one of the raw materials for geopolymers.

[0004] Slag is a granulated byproduct obtained by quenching the molten waste discharged from the blast furnace during the pig iron smelting process. Most of the particles of granulated blast furnace slag are irregular in shape, mostly needle-like or flat. After grinding to a certain particle size distribution, they can meet the corresponding potential activity index requirements. The main components of slag are CaO, SiO2, Al2O3 and other substances, which are similar to the composition of cement. It can be used as a raw material for building materials, mostly used to produce slag cement or as an admixture for concrete. It can save energy and reduce the greenhouse effect caused by CO2 emissions and environmental pollution caused by waste slag stacking. Blast furnace heavy slag is mainly used to replace natural crushed stone in roadbed landfill and other projects, and is also used as coarse aggregate for concrete.

[0005] Modified fiber is to use chemical reagents to depolymerize the high molecular polymer in the waste fiber at high temperature and convert it into monomers or oligomers, and then modify the raw materials through a series of processes such as polymerization, granulation, spinning, and weaving to obtain new fiber products. In life and production, there are waste fiber materials that cannot be effectively recycled, which will lead to serious waste of resources and environmental pollution. The storage of these solid wastes not only occupies a large amount of land resources, but also causes soil, water and air pollution, seriously endangering the ecological environment. Modify the raw materials and obtain new fiber products to realize the functional changes and recycling of waste fibers. More importantly, by comprehensively improving the mechanical properties and parameter indicators of modified fibers, new geotechnical materials can be made and applied to practical engineering, which has broad application prospects.

[0006] Geopolymer cementitious materials are a new type of alkali-activated cementitious materials. They usually use natural mineral materials containing aluminosilicates (such as metakaolin) and industrial solid waste (such as fly ash, slag, steel slag, red mud and various tailings, etc.) as the main materials. Under the action of alkali activators at room temperature or slightly higher temperatures, they are depolymerized and polycondensed to form a cementitious material with a three-dimensional spatial network structure composed of SiO4 and AlO4 tetrahedral structural units through shared oxygen alternating bonds. Geopolymers can not only fully utilize industrial solid waste as raw materials to achieve large-scale resource recycling of solid waste, but also have a simple preparation process and low production energy consumption, which can reduce CO2 emissions by 60%-80%. It is a type of advanced green building material with huge development potential. The three-dimensional network structure of geopolymer materials determines its excellent performance and thus determines its versatility. As a new type of material, geopolymer has been widely used in building cementitious materials, thermal insulation materials, composite materials, aerospace and fixation of toxic heavy metal ions in industrial wastewater and waste residues. Its energy-saving and environmentally friendly characteristics in the preparation process give it greater advantages over cement production, and its durability is much better than cement. Summary of the invention

[0007] In order to make full use of fly ash resources, the present invention proposes a fiber-fly ash-based polymer cementitious material and a preparation method thereof, which can efficiently utilize fly ash resources while reducing pollution. The obtained fiber-fly ash geopolymer cementitious material and the two-grinding-one-burning production process of traditional cement can reduce carbon emissions by about 80% and energy consumption by 60%, and have satisfactory mechanical properties.

[0008] The first object of the present invention is to provide a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by weight:

[0009] In the geopolymer cementitious material, by weight percentage, fly ash is 40-60 parts; slag is 15-35 parts; steel slag is 10-30 parts; alkali activator accounts for 4-20 parts of the cementitious material; water accounts for 30-38 parts of the cementitious material; and modified fiber accounts for 0-2 parts of the cementitious material.

[0010] Preferably, in the geopolymer gelling material, by mass percentage, there are 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 20 parts of the alkali activator by mass of the gel material (modulus 1.4), 1.6 parts of the modified fiber by mass of the gel material, and the water-to-cement ratio is 36 parts by mass of the gel material.

[0011] The second object of the present invention is to provide a method for preparing a fly ash-based polymer gelling material, which specifically comprises the following steps:

[0012] Step (1) uniformly mixing the modified fiber with fly ash, steel slag and slag to obtain a precursor modified fiber powder;

[0013] Step (2) sodium silicate solution, analytically pure sodium hydroxide and water are prepared into an alkaline activator solution with a modulus of 1.2-2 and a Baume degree of 30°Be, and the solution is cooled and stored in a bottle for standing;

[0014] Step (3) fully mixing the above-mentioned precursor modified fiber powder and the alkali activator to obtain a slurry, then injecting the slurry into a mold, placing it on a cement mortar vibrating table and vibrating it for 3-5 minutes;

[0015] In step (4), the sample is cured in a curing box to obtain a modified fiber-fly ash-based polymer gelling material.

[0016] Preferably, the stirring speed in step (1), step (2) and step (3) is 120 to 150 r / min.

[0017] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0018] In the prior art, cement-based cementitious materials are often used to reinforce soft soil layers, which will face the problems of high energy consumption and high carbon emissions, and cause multiple negative impacts on the ecological environment. The fly ash used in the present invention is a powder produced by thermal power generation, which can promote the utilization of solid waste resources, realize waste recycling, and is conducive to saving energy consumption, and partially replace cement; combining slag and steel slag alkali-activated geopolymer cementitious materials for soft soil reinforcement can also achieve a curing effect equivalent to that of cement-based cementitious materials, and can effectively solve the economic problems of solid waste resource storage and resource utilization; and adding modified fiber consolidation method to geopolymer cementitious materials can greatly make up for the lack of ductility of geopolymer cementitious materials, better improve its crack resistance, and have a good curing effect. In summary, the present invention is a high-performance material with both coagulation flow characteristics and mechanical strength characteristics. The material is simple and economical, the construction is quick and convenient, and the curing effect is reliable and stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flowchart of a method for preparing a fiber-fly ash-based polymer cementitious material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0020] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the following description, the same modules are represented by the same reference numerals. In the case of the same reference numerals, their names and functions are also the same. Therefore, the detailed description thereof will not be repeated.

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not constitute a limitation of the present invention.

[0022] A modified fiber-fly ash-based polymer gelling material comprises the following components in parts by mass: 40-60 parts of fly ash; 15-35 parts of slag; 10-30 parts of steel slag; 4-20 parts of alkali activator in terms of the mass of the solid gel material; 30-38 parts of water in terms of the mass of the solid gel material; and 0-2 parts of modified fiber in terms of the mass of the solid gel material.

[0023] The fly ash has a particle size of 1-90 μm and a specific surface area of ​​320-450 m 2 / kg or density of 1.7-2.2g / cm 3 The particle size of the slag is 1-110 μm, and the specific surface area is 500-520 m 2 / kg or density 2.8-3.1g / cm 3 The particle size of the steel slag is 5-140 μm, and the specific surface area is 470-480 m 2 / kg or density 3.1-3.2g / cm 3The alkali stimulant is a modified sodium silicate solution prepared by mixing a sodium silicate solution and an analytically pure sodium hydroxide. The sodium silicate solution accounts for 4-20 parts of the mass of the solid gel material and has a modulus of 1.2-2.0. The original sodium silicate solution includes the following components in mass fractions: 30.5-35.5% silicon dioxide, 8.5-10.5% sodium hydroxide and a density of 1.39-1.42%.

[0024] A modified fiber-fly ash-based polymer gelling material comprises the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator, 36 parts of water accounting for the mass of the solid gel material, and 1.2 parts of modified fiber accounting for the mass of the solid gel material.

[0025] A method for preparing a modified fiber-fly ash-based polymer gelling material specifically comprises the following steps:

[0026] Step (1) uniformly mixing the modified fiber with fly ash, steel slag and slag to obtain a precursor modified fiber powder;

[0027] Step (2) the original sodium silicate solution, analytically pure sodium hydroxide and water are prepared into an alkaline activator sodium silicate solution with a modulus of 1.2-2 and a Baume degree of 30°Be, and the solution is cooled and stored in a bottle for standing;

[0028] Step (3) fully mixing the above-mentioned precursor modified fiber powder and the alkali activator to obtain a slurry, then injecting the slurry into a mold, and placing it on a cement mortar vibration table to vibrate for 5-10 minutes;

[0029] In step (4), the sample is cured in a curing box to obtain a modified fiber-fly ash-based polymer gelling material.

[0030] The stirring speed in the above steps (1), (2) and (3) is 120 to 150 r / min.

[0031] Various testing methods and processes:

[0032] The flowability of geopolymer slurry is measured with reference to Standard Test Method for Flow Consistency of Controlled Low Strength Material (ASTM-D6103-97). The stirred geopolymer slurry is quickly injected into a cylindrical mold (inner diameter 76mm×height 150mm). The cylindrical barrel is quickly lifted vertically within 4 seconds to allow the mixture in the barrel to expand freely under the action of gravity. When the mixture has no obvious flow characteristics or after 5 minutes, the fluidity values ​​are immediately measured in different directions with a ruler or triangle ruler, and the average value is taken as the fluidity of the geopolymer neat slurry.

[0033] The setting time of geopolymer slurry is measured in accordance with the standard "Test Method for Water Consistency, Setting Time and Stability of Cement Standard Consistency" (GBT1346-2011). The first measurement is carried out 30 minutes after the specimen is cured in the moisture curing box and water is added. During the measurement, the test mold is taken out of the moisture curing box and placed under the test needle, and the test needle is lowered to contact the surface of the cement slurry. After tightening the screw for 1-2 seconds, it is suddenly released, and the test needle sinks vertically and freely into the cement slurry. Observe the pointer reading when the test needle stops sinking or releases the test needle for 30 seconds. When approaching the initial setting time, measure once every 5 minutes (or shorter time). When the test needle sinks to 4±1mm from the bottom plate, the cement reaches the initial setting state; the time from the cement is completely added to the water to the initial setting state is the initial setting time of the cement, expressed in minutes.

[0034] The unconfined compressive strength is tested with reference to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021). The evenly stirred geopolymer slurry is divided into three layers and loaded into a 50×50×50mm three-piece mold and vibrated for 30 seconds. It is quickly placed in a curing room and cured for 2 hours (temperature 20±1℃, relative humidity not less than 90%), then demolded. The unconfined compressive strength of the block is tested after curing for 7d, 14d, and 28d. It is loaded at a rate of 0.3MPa / s using a fully automatic pressure testing machine, and the average value of the three specimens is taken as the result. If the deviation of a test block from the mean is greater than ±10%, this group of test blocks is redone.

[0035] Test results: The initial setting and final setting time of the modified fiber-fly ash-based polymer obtained according to the proportion of the components in this group are 235min and 275min respectively. According to the "General Portland Cement" (GB175-2007) specification, it can meet the requirements of cement paste for initial setting time ≥45min and final setting time ≤6h. The fluidity is 195mm, which has good slurry fluidity. The unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d is 26.03MPa, 39.33MPa, and 40.50MPa. Fly ash, steel slag, and slag show synergistic effects under the stimulation of sodium silicate solution, an alkaline activator. Slag and steel slag release a large amount of Ca in sodium silicate solution. 2 + These ions combine with silicon (aluminum) oxygen tetrahedrons formed by the hydration of fly ash to form amorphous calcium silicate hydrate (CSH) and calcium aluminum silicate hydrate (CASH) gel, thereby forming a dense and compact microstructure, providing the required strength for the sample.

[0036] Example 1

[0037] This embodiment provides a fly ash-based polymer gelling material, comprising the following components in parts by weight:

[0038] 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), and 36 parts of water.

[0039] The activator is a modified sodium silicate solution prepared by mixing a sodium silicate solution and sodium hydroxide particles. The sodium silicate solution includes the following components by mass fraction: 32.18% silicon dioxide (SiO2), 9.99% sodium oxide (Na2O) and a density of 1.41; the sodium hydroxide particles are analytically pure and have a solid content of 99%; the modulus of the original sodium silicate solution is 2.0.

[0040] The particle size of fly ash is less than 15 μm; the specific surface area of ​​fly ash is 510.20 m 2 / kg or density is 2.10g / cm 3 The chemical composition is Al2O336.8%, SiO245.10%, CaO4.5%, MgO0.85%, Fe2O30.85%, SO31.2%, Na2O0.75%, and the loss on ignition is 9.95%.

[0041] The particle size of slag is less than 105μm; the specific surface area of ​​slag is 508.00m 2 / kg or density is 2.90g / cm 3 The chemical composition is SiO233.22%, CaO39.51%, Al2O316.04%, MgO8.96%, SO31.8%, and the loss on ignition is 0.7%.

[0042] The particle size of steel slag is less than 120μm; the specific surface area of ​​steel slag is 474.00m 2 / kg or density is 3.18g / cm 3 The chemical components are CaO 38.72%, SiO2 19.40%, Fe2O3 22.42%, Al2O3 6.37%, MgO 6.05%, MnO 2.1%, SO3 0.81%, others 1.87%, and the remainder is loss on ignition.

[0043] The preparation method specifically comprises the following steps:

[0044] Step (1) The modified fiber is mixed evenly with fly ash, steel slag and slag to obtain a precursor modified fiber powder:

[0045] Step (2) sodium silicate solution, analytically pure sodium hydroxide and water are prepared into an alkaline activator sodium silicate solution with a modulus of 1.2-2 and a Baume degree of 30°Be, and the solution is cooled and stored in a bottle for standing;

[0046] Step (3) fully mixing the above-mentioned precursor modified fiber powder and the alkali activator to obtain a slurry, then injecting the slurry into a mold, placing it on a cement mortar vibrating table and vibrating it for 3-5 minutes;

[0047] Step (4) the sample is cured in a curing box to obtain a modified fiber-fly ash-based polymer gelling material;

[0048] The prepared modified fiber-fly ash-based polymer slurry will be tested for its slurry fluidity, initial setting and final setting time, and its unconfined compressive strength at 7d, 14d and 28d under standard curing conditions (20±1°C, humidity 85%).

[0049] Example 2

[0050] The present embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 40 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), and 36 parts of water.

[0051] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0052] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 232min and 271min respectively, the fluidity is 192mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 24.02MPa, 37.18MPa, and 38.14MPa.

[0053] Example 3

[0054] This embodiment provides a modified fiber-fly ash-based polymer gelling material, including the following components in parts by mass: 60 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), and 36 parts of water.

[0055] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0056] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 237min and 278min respectively, the fluidity is 198mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 25.13MPa, 38.76MPa, and 39.18MPa.

[0057] Example 4

[0058] The present embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 5 parts of slag, 16 parts of activator (modulus 1.4), and 36 parts of water.

[0059] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0060] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 239min and 277min respectively, the fluidity is 199mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 22.12MPa, 31.09MPa, and 35.73MPa.

[0061] Example 5

[0062] The present embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 15 parts of slag, 16 parts of activator (modulus 1.4), and 36 parts of water.

[0063] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0064] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 237min and 276min respectively, the fluidity is 197mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 24.43MPa, 34.56MPa, and 37.49MPa.

[0065] Example 6

[0066] The present embodiment provides a modified fiber-fly ash-based polymer cementitious material, comprising the following components in parts by mass: 50 parts of fly ash, 5 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), and 36 parts of water.

[0067] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0068] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 236 min and 277 min respectively, the fluidity is 196 mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 25.41 MPa, 38.21 MPa, and 39.88 MPa.

[0069] Example 7

[0070] The present embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 20 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), and 36 parts of water.

[0071] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0072] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 232min and 271min respectively, the fluidity is 189mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 22.16MPa, 29.37MPa, and 33.42MPa.

[0073] Example 8

[0074] This embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 12 parts of activator (modulus 1.4), and 36 parts of water.

[0075] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0076] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 236 min and 277 min respectively, the fluidity is 196 mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 20.56 MPa, 32.43 MPa, and 35.69 MPa.

[0077] Example 9

[0078] This embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 20 parts of activator (modulus 1.4), and 36 parts of water.

[0079] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0080] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 234min and 273min respectively, the fluidity is 193mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 27.43MPa, 40.16MPa, and 42.13MPa.

[0081] Example 10

[0082] The present embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.2), and 36 parts of water.

[0083] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0084] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 236 min and 277 min respectively, the fluidity is 197 mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 25.16 MPa, 38.49 MPa, and 40.21 MPa.

[0085] Embodiment 11

[0086] The present embodiment provides a modified fiber-fly ash-based polymer cementitious material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.6), and 36 parts of water.

[0087] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0088] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 234min and 275min respectively, the fluidity is 194mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 27.23MPa, 39.56MPa, and 41.21MPa.

[0089] Example 12

[0090] The present embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), and 34 parts of water.

[0091] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0092] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 232 min and 271 min respectively, the fluidity is 184 mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 23.23 MPa, 33.56 MPa, and 35.21 MPa.

[0093] Example 13

[0094] The present embodiment provides a modified fiber-fly ash-based polymer gelling material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.6), and 38 parts of water.

[0095] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0096] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 239 min and 281 min respectively, the fluidity is 206 mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 22.23 MPa, 32.96 MPa, and 34.41 MPa.

[0097] Comparative Example 1

[0098] The present embodiment provides a modified fiber-fly ash-based polymer cementitious material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), 36 parts of water, and 0.4 parts of modified fiber.

[0099] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0100] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 231 min and 272 min respectively, the fluidity is 187 mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 34.61 MPa, 44.56 MPa, and 47.63 MPa.

[0101] Comparative Example 2

[0102] The present embodiment provides a modified fiber-fly ash-based polymer cementitious material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.6), 36 parts of water, and 0.8 parts of modified fiber.

[0103] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0104] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 228min and 270min respectively, the fluidity is 185mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 39.45MPa, 47.12MPa, and 49.65MPa.

[0105] Comparative Example 3

[0106] The present embodiment provides a modified fiber-fly ash-based polymer cementitious material, comprising the following components in parts by mass: 50 parts of fly ash, 10 parts of steel slag, 25 parts of slag, 16 parts of activator (modulus 1.4), 36 parts of water, and 1.2 parts of modified fiber.

[0107] The physical and chemical indicators of the components are the same as those in Example 1; the preparation method of the modified fiber-fly ash-based polymer gelling material is the same as that in Example 1.

[0108] Measurement results: The initial and final setting times of the modified fiber-fly ash-based polymer obtained according to the proportion of components in this group are 223min and 266min respectively, the fluidity is 181mm, and the unconfined compressive strength of the test block under standard curing conditions of 7d, 14d, and 28d are 46.51MPa, 49.43MPa, and 52.56MPa.

[0109] According to the comparison of the material properties of the above comparative examples and embodiments, considering the economic efficiency, working performance and strength growth benefits, the mass fraction of fly ash should be about 50 parts, the mass fraction of steel slag should be less than 15 parts, and the mass fraction of slag should be greater than 25 parts. When the mass fraction of the activator solution is 16-20 parts, it helps to increase the activation degree of the hydration reaction between the geopolymer gelling substances, thereby improving the overall strength of the modified fiber-fly ash-based polymer. The addition of modified fiber materials can improve the overall strength of the modified fiber-fly ash-based polymer material, which increases with the increase of the modified fiber content, but is not conducive to the geopolymer slurry to obtain better fluidity. The slurry coagulation rate increases with the increase of the amount of water added. Increasing the amount of water added can improve the fluidity of the geopolymer slurry, but generally speaking, increasing the amount of water added is not conducive to the improvement of the strength of the geopolymer.

[0110] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps described in the disclosure of the present invention can be performed in parallel, sequentially or in different orders, as long as the desired results of the technical solution disclosed in the present invention can be achieved, and this document does not limit this.

[0111] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A modified fiber-fly ash-based polymer gelling material, characterized in that: The composition comprises the following components in parts by weight: 40-60 parts of fly ash; 15-35 parts of slag; 10-30 parts of steel slag; and 4-20 parts of alkali activator in the weight of the solid gel material. The water accounts for 30-38 parts by weight of the solid gel material; the modified fiber accounts for 0-2 parts by weight of the solid gel material.

2. The modified fiber-fly ash-based polymer gelling material according to claim 1, characterized in that: The fly ash has a particle size of 1-90 μm and a specific surface area of ​​320-450 m 2 / kg or density of 1.7-2.2g / cm 3 .

3. The modified fiber-fly ash-based polymer gelling material according to claim 1, characterized in that: The particle size of the slag is 1-110 μm, and the specific surface area is 500-520 m 2 / kg or density 2.8-3.1g / cm 3 .

4. The modified fiber-fly ash-based polymer gelling material according to claim 1, characterized in that: The particle size of the steel slag is 5-140 μm, and the specific surface area is 470-480 m 2 / kg or density 3.1-3.2g / cm 3 .

5. The modified fiber-fly ash-based polymer gelling material according to claim 1, wherein the alkali activator is a modified sodium silicate solution prepared by mixing a sodium silicate solution and analytically pure sodium hydroxide, the sodium silicate solution is 4-20 parts by mass of the solid gel material, and the modulus is 1.2-2.

0.

6. The fly ash-based polymer cementitious material according to claim 1, characterized in that: The sodium silicate original solution comprises the following components in mass fractions: 30.5-35.5% of silicon dioxide, 8.5-10.5% of sodium hydroxide and a density of 1.39-1.42%.

7. The modified fiber-fly ash-based polymer gelling material according to claim 1, characterized in that: Calculated by mass percentage, the fly ash accounts for 50 parts, the steel slag accounts for 10 parts, the slag accounts for 25 parts, the activator accounts for 16 parts, the water accounts for 36 parts of the solid gel material, and the modified fiber accounts for 1.2 parts of the solid gel material.

8. A method for preparing the modified fiber-fly ash-based polymer cementitious material according to any one of claims 1 to 7, characterized in that: The specific steps include: Step (1) uniformly mixing the modified fiber with fly ash, steel slag and slag to obtain a precursor modified fiber powder; Step (2) the original sodium silicate solution, analytically pure sodium hydroxide and water are prepared into an alkaline activator sodium silicate solution with a modulus of 1.2-2 and a Baume degree of 30°Be, and the solution is cooled and stored in a bottle for standing; Step (3) fully mixing the above-mentioned precursor modified fiber powder and the alkali activator to obtain a slurry, then injecting the slurry into a mold, and placing it on a cement mortar vibration table to vibrate for 5-10 minutes; In step (4), the sample is cured in a curing box to obtain a modified fiber-fly ash-based polymer gelling material.

9. The method for preparing the modified fiber-fly ash-based polymer gelling material according to claim 8, characterized in that: The stirring in step (1), step (2) and step (3) has a rotation speed of 120 to 150 r / min.

Citation Information

Cited By

  • Preparation process of high-toughness anti-cracking alkali-activated geopolymer cementing material

    CN120289108A

  • Fly ash-based geopolymer concrete and preparation method thereof

    CN120943569A